What teachers and students say about Mathematics and their Teaching (Research, Society and Development, 2019)
Faced with the challenges that the discipline of Mathematics and its Teaching present and, understanding the process of teaching and learning as a social interaction, this article looks at the mathematical knowledge from the perspective of the Theory of Social Representations in order to understand which representations, socially constructed and shared by students and teachers about Mathematics and its Teaching conform the process of teaching and learning of mathematical concepts within the scope of teaching practice. We outline the present work in the identification of Mathematics and its Teaching as representational objects for the social groups that participate in the research through the application of questionnaires and with the help of EVOC software. The results show that mathematics and its teaching are representational and relevant to this social group, both in social, cognitive and affective aspects. The conclusions indicate that for an effective teaching of Mathematics it is not enough to modify the didactic actions only if we maintain the same social representations.